# How would u simplify this if possible? 2 square root of 3 + square root of 27 - square root of 1/3

### 2 Answers | Add Yours

To simplify 2sqrt3+sqrt27-sqrt(1/3)

Solution:

sqrt27 = sqrt(3*3*3) = 3 sqrt3

sqrt(1/3) = 1/sqrt3 = sqrt3/(sqrt3)^2 = (1/3) sqrt3Therefore

2sqrt3+sqrt27-sqrt(1/3) =2xrt3+3sqrt3-(1/3)sqrt3 = (2+3-1/3)sqrt3

=(5-1/3) sqrt3

= (14/3) sqrt3

Simplify:

2sqrt(3)+sqrt(27)-1/sqrt(3)

= 2sqrt(3)+sqrt(3*3*3)-1/sqrt(3)

=2qrt(3)+3sqrt(3)-1/sqrt(3)

Multiply and divide by sqrt(3)

=[2(3) + 3(3)- 1]/sqrt(3)

= (6+9-1)/sqrt(3) = 14/sqrt(3)= (14/3)sqrt(3)